Reaksi Pasar Terhadap Kenaikan Bank Indonesia 7-Day Reverse Repo Rate Tanggal 15 Agustus 2018 - Rian Mahendra, I Kadek; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
This study aims to examine the information content by explaining at the market reaction to the announcement of the 7-Day Reverse Repo Rate BI increase on August 15 2018 as measured by the abnormal return and trading volume activity. This research is an event study with an observation period of 7 exchange workdays, namely three days before (t-3), event date (t0), and three days after the event (t + 3). The sample is a company incorporated in the LQ45 Index for the period of August 2018 to January 2019. The method of determining the sample is a purposive sampling technique. The data analysis technique uses paired samples t-test and Wilcoxon signed rank test. The results showed a difference in average abnormal return and average trading volume activity before and after a 7-Day Reverse Repo Rate BI increase on August 15, 2018. This indicates that the event has information content. Keywords : Event study, abnormal return, trading volume activity